Երևանի փողոցների կահավորման դետալների ներկա վիճակն ու բարելավման հնարավորությունները - Մարտին Հարությունյան (ՀՀ ԳԱԱ հրատ.)
В статье содержится краткий обзор уличного обустройства Еревана (скамейки, остановки/кабинки, информационные таблички общественного транспорта, рекламные щиты), нынешнего статуса и возможности его улучшения.The article contains a brief review of Yerevan’s street facilities (benches,stops/booths, public transport information boards, billboards and information boards), their current status and improvement possibilities.
Keywords: Fine Arts; Decorative arts; Applied arts; Decoration and ornament; Architecture